Worker Protection Laws Against Safety Of Health Services During Covid-19 Pandemic - Aprilia Widya; Maramis, Ronny A.; Anis, Friend H. (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Abstract: This study aims to analyze the protection and law enforcement of the safety of medical personnel in health services during the COVID-19 pandemic. The research method used in this research is normative juridical. The approach used in this research is the conceptual approach and the statutory approach. Sources and types of data used are secondary data. Secondary data collection is done by conducting a literature study. The results of the study show that the law enforcement process against the laws and regulations regarding the safety of medical personnel in health services during the COVID-19 pandemic has not been properly enforced so that in its implementation there are many cases of medical personnel who are exposed and died due to COVID-19, so that the rights of the rights of health workers during the pandemic are still neglected and have not been fulfilled. The factors that cause such as: lack of Personal Protective Equipment (PPE) including masks (N95), eye protection, gloves and long gowns (gown), lack of medical personnel, heavy workload, excessive and unbalanced working hours with fixed incentives, inadequate work environment and lack of attention from the central government when medical personnel provide health services. And also in the process of providing incentives and compensation for death, it was found that there were internal obstacles that resulted in the giving process not running in accordance with the established rules. Keywords: Legal Protection; Health Service; Medical Workers Safety; Covid-19